The shoulder profile in team handball - Laudner, K. G.; Hermassi, S.; Schwesig, R. (Handball Sports Medicine, 2018)
Handball athletes are routinely exposed to direct and indirect trauma to their throwing shoulder. Due to the violent and repetitive nature of the throwing motion, these athletes also commonly present with functional adaptations of the throwing shoulder that stem from osseous and soft tissue structural changes. These functional adaptations may include decreased internal rotation ROM, increased external rotation ROM, decreased external rotation strength, and scapular dyskinesis. Although these are common adaptations among handball athletes, such changes can have detrimental effects, often leading to injury and time lost from competition, when they are not managed correctly through preventative exercises or with drastic decreases in playing volume.